2020
DOI: 10.1039/d0dt02379e
|View full text |Cite
|
Sign up to set email alerts
|

Speciation, thermodynamics and structure of Np(v) oxalate complexes in aqueous solution

Abstract: The speciation, thermodynamics and structure of the NpO2+ complexes with oxalate are studied by different spectroscopic techniques. Near infrared absorption spectroscopy (Vis/NIR) is used to investigate complexation reactions as a...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 62 publications
2
2
0
Order By: Relevance
“…In contrast, the C c distance in the malonate complexes are by 0.50–0.58 Å longer, indicating the formation of chelate rings involving one O atom of each COO – group. Furthermore, the C c distance in the NpO 2 (Mal) n 1–2 n complexes is in excellent agreement with the results for Np­(V) oxalate complexes also displaying side-on coordination ( C c : 3.32 ± 0.06 Å) …”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…In contrast, the C c distance in the malonate complexes are by 0.50–0.58 Å longer, indicating the formation of chelate rings involving one O atom of each COO – group. Furthermore, the C c distance in the NpO 2 (Mal) n 1–2 n complexes is in excellent agreement with the results for Np­(V) oxalate complexes also displaying side-on coordination ( C c : 3.32 ± 0.06 Å) …”
Section: Resultssupporting
confidence: 86%
“…To investigate steric effects, the results for the Np­(V) complexes of the present work are compared to recently published data for the complexation of Np­(V) with oxalate (Ox 2– ) . A comparison of log β n ° (Θ) of oxalate, malonate, and succinate reveals a successive decrease of the complex stability with increasing C-backbone of the dicarboxylates.…”
Section: Resultssupporting
confidence: 81%
“…13 The vis-NIR spectrum of Np( v ) in wet RTIL shows a prominent peak at 976 nm, characteristic of the ion whereas for dry RTIL an additional peak at 1002 nm was seen along with the 971 peak, which can be attributed to its complexation with different ligands. 50–52 Dong et al , 41 have also observed few peaks in the Np( v ) vis-NIR spectrum in dry C 4 mim.NTf 2 and assigned their occurrence to the Np–hydroxo or carbonato complexes. 41 Though one would be tempted to conclude accordingly, our studies for CCI interactions between Np( v ) and U( vi ) in dry RTIL and wet RTIL contradict these peak assignments.…”
Section: Resultsmentioning
confidence: 95%
“…At the Priroda-optimized geometries, electronic structures were calculated in a tetrahydrofuran (THF) solution by using the ADF 2014 program . This approximation has proven to be reliable as re-optimizations have only a very slight effect on the structural parameters and molecular properties. The default convergence criterion of 10 –6 au was used, and an integration parameter of 6.0 was applied. The solvation was taken into account using the Conductor-Like Screening Model, COSMO. , A dielectric constant of 7.58 was applied for THF, associated with the E surf -type of cavity.…”
Section: Computational Detailsmentioning
confidence: 99%